Seni Berbicara Tokoh Dalam Novel Wanita Idaman Karya Robert Goolrick: Kajian Retorika - Resa Resa; Misnawati Misnawati; Yuliati Eka Asi; Patrisia Cuesdeyeni; Rensyna Rensyna; Dan Silvana (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The art of speaking characters in Wanita Idaman novels (Translated by Meggy P. Soedjatmiko) by Robert Goolrick: Rhetorical Study this study aims to describe the art of speaking characters based on the study of rhetorical types of dialogue (The art of speaking in discussion, debriefing, negotiation, conversation, and debate) and depiction of the character’s based on the dialogue of the characters in Wanita Idaman novels by Robert Goolrick. This study uses a literary work approach based on the art of speaking figures using the study of dialogic rhetoric. The study of dialogic rhetoric consists of five types of speaking arts, debriefing, negotiation, conversation, and debate. The project of research are the characters Catherine Land, Ralp Truitt, and Mrs. Larsen in the novel Wanita Idaman which was published on July 29 2010 with 406 pages thick. The data techniques. Data analysis was carried out using qualitative analysis techniques. The research rsult obtained in this study are in the form of studie on characters or characters Catherine Land, Ralp Truitt, and Mrs. Larsen based on the art of speaking the study of dialogic rhetoric which consists of the art of speaking discussion, question and answer, negotiation, conversation, ad debate in the novel Wanita Idaman by Robert Goolrick.